Introduction - Herbert, Jeannie (The Australian Journal of Indigenous Education, 2013)
This Special Issue of the Australian Journal of Indigenous Education presents a unique collection of nine articles representing the initial outputs from the Remote Education Systems’ (RES) 5-year project to research and identify ways in which education systems might respond more effectively to Aboriginal and Torres Strait Islander expectations, aspirations and learning needs. The project is unique for two reasons: (1) its focus on one of the most critical and complex aspects of the Australian education landscape — the need for systemic change in improving the education outcomes of Indigenous students living in remote locations throughout the nation; and (2) there is sufficient time for researchers to meaningfully engage with the diversity of remote-based stakeholders — educators, parents, students and the wider community – in order to obtain their viewpoints concerning the value of the remote-based education service delivery provided in their schools.